Makna Awwala bait pada Q.S Ali Imran Ayat 96 (Perspektif Abdul Qadir Al-Jailani Dalam Tafsir Al-Jailani) - Muhammad Zainuri Alkahfi Hasibuan; Halimatussaâ€™diyah Halimatussaâ€™diyah; Kamaruddin Kamaruddin (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2023)
This article is entitled "The Meaning of Awwala bait in Q.S Ali Imran Verse 96 (Abdul Qadir Al-Jailani's Perspective in Tafsir Al-Jailani)â€. God built the first house for humans, in order to understand that the presence of God's house raises awareness that only God has the right to be worshiped and glorified by humans. Sheikh Abdul Qadir named this as Tawhid adz-Dzatiy, or the oneness of Allah alone because everything He has created will return and surrender only to Allah. Allah's first house (Awwala Bait) is bestowed by Allah with broad blessings and becomes a guide for the whole world. This study aims to examine the meaning of the awwala stanza in Q.S Ali Imran verse 96 regarding the house of Allah which is not only introduced in physical or outward form. But it also touches the nature behind the house of Allah SWT. which penetrates to the wisdom of the presence of God's first home on earth for humans. In reviewing this research using the library research method (library) with the form of qualitative data. By exploring the views of Shaykh Abdul Qadir Al-Jailani which he outlined in a monumental work, Tafsir Al-Jailani. So that the data reviewed is in the form of text studies, books that are relevant to the subject matter, books of commentary, journals, theses, and scientific papers that are relevant to the discussion of research. Furthermore, the method applied to study Al-Jailani's interpretation uses the maudhu'i method approach by collecting and studying verses related to the theme of meaning (awwala bait). The data collection technique is by data reduction, data presentation, and drawing conclusions. The results that were concluded from research regarding the meaning of the awwala verse in Q.S Ali Imran verse 96 understand that, Allah's first house was not limited to a physical building. However, Shaykh Abdul Qadir explained that the presence of Allah's first house provides broad blessings and becomes a guide to Allah for the whole world. So as to obtain closeness based on love for the owner of the house, namely Allah Rabb Al-'Alamiin.